Dynamics of the inland penetrating Indian monsoon depressions - K Sandhyavijayan; K. P. Sooraj; E. Suhas; Pascal Terray (Climate Dynamics, 2026)

Uncertainty in projected changes of Indian Summer Monsoon Rainfall by CMIP6 models - K.P. Sooraj; Pascal Terray; Ajinkya M. Aswale (Atmospheric Research, 2026)

Anatomy of the Indian summer monsoon and ENSO relationship in a state-of-the-art CGCM: role of the tropical Atlantic Ocean - Pascal Terray; Ligin Joseph; K. P. Sooraj (Climate Dynamics, 2023)

Tropical Indian Ocean and ENSO relationships in a changed climate - Shamal Marathe; Pascal Terray; Ashok Karumuri (Climate Dynamics, 2021)

Factors affecting adult body condition in the endangered northern rockhopper penguin - Karine Delord; Cédric Cotté; Pascal Terray; Charles-André Bost; Henri Weimerskirch; Christophe Barbraud (Marine Biology, 2021)

Anatomy of the Indian Summer Monsoon and ENSO relationships in state-of-the-art CGCMs: role of the tropical Indian Ocean - Pascal Terray; K. P. Sooraj; Sébastien Masson; Chloé Prodhomme (Climate Dynamics, 2021)

Mid-Holocene to present-day evolution of the Indian monsoon in transient global simulations - Julien Crétat; Pascale Braconnot; Pascal Terray; Olivier Marti; Fabrizio Falasca (Climate Dynamics, 2020)

Dynamics of rainfall extremes over India: A new perspective - KP Sooraj; Pascal Terray; Anokha Shilin; Milind Mujumdar (International Journal of Climatology, 2020)
A comprehensive analysis of the role of Indo‐Pakistan arid region (IPAR) in modulating the boreal summer heavy extreme rainfall events over monsoon core zone (MCZ over Indian subcontinent) at subseasonal to daily time scales is presented. The objective is to bring new perspectives on the dynamics of such rainfall extremes. Time‐lagged composite analysis shows the clustering of Monsoon Intra‐Seasonal Oscillation with monsoon rainfall daily extremes. However, our results additionally bring out the distinct role of surface thermal forcing and moist processes over IPAR as another potential and significant precursor, 16–10 days in advance, causing monsoon rainfall daily extremes over MCZ. Further analysis reveals that the warming over IPAR is initially found in the northern part of the domain, 20–15 days before the rainfall events over MCZ and is triggered by subtropical‐midlatitude interactions characterized by the intrusion of a midlatitude (i.e., Eurasian) atmospheric wave train into the Asian domain. Our analysis further reveals strong moist static energy (MSE) build‐up over the IPAR 12 days in advance, which is initially dominated by anomalous warming in the lower atmosphere, but with an incremental contribution of low‐level specific humidity as we moved forward in time towards the rainfall event. Hydrodynamic‐longwave radiative teleconnections are the primary mechanism for the persistence of the surface warming and MSE buildup over IPAR after the initial intrusion of the Eurasian wave train. The persistent warming over IPAR reinforces the land‐sea contrast between the Middle East and western equatorial Indian Ocean to its south, and this subsequently leads to pressure anomalies and monsoon circulation changes through geostrophic wind adjustment, thus enhancing westerlies over Arabian Sea. All these factors lead to the development of a gigantic monsoon trough over central India thus causing the rainfall extremes over MCZ through the genesis of synoptic vortices.

Modulations of the Indian summer monsoon by the hot subtropical deserts: insights from coupled sensitivity experiments - K. P. Sooraj; Pascal Terray; Sébastien Masson; Julien Crétat (Climate Dynamics, 2019)

Intrinsic precursors and timescale of the tropical Indian Ocean Dipole: insights from partially decoupled numerical experiment - Julien Crétat; Pascal Terray; Sébastien Masson; K. P. Sooraj (Climate Dynamics, 2018)

Indian Ocean and Indian summer monsoon: relationships without ENSO in ocean–atmosphere coupled simulations - Julien Crétat; Pascal Terray; Sébastien Masson; K. P. Sooraj; Mathew Koll Roxy (Climate Dynamics, 2017)

Roles of land surface albedo and horizontal resolution on the Indian summer monsoon biases in a coupled ocean–atmosphere tropical-channel model - Guillaume Samson; Sébastien Masson; Fabien Durand; Pascal Terray; Sarah Berthet; Swen Jullien (Climate Dynamics, 2017)

Control of shortwave radiation parameterization on tropical climate SST-forced simulation - Julien Crétat; Sébastien Masson; Sarah Berthet; Guillaume Samson; Pascal Terray; Jimy Dudhia; Françoise Pinsard; Christophe Hourdin (Climate Dynamics, 2016)

Sub-seasonal behaviour of Asian summer monsoon under a changing climate: assessments using CMIP5 models - K. P. Sooraj; Pascal Terray; Prince Xavier (Climate Dynamics, 2016)

Impacts of Indian and Atlantic oceans on ENSO in a comprehensive modeling framework - Pascal Terray; Sébastien Masson; Chloé Prodhomme; Mathew Koll Roxy; K. P. Sooraj (Climate Dynamics, 2016)

Global warming and the weakening of the Asian summer monsoon circulation: assessments from the CMIP5 models - K. P. Sooraj; Pascal Terray; M. Mujumdar (Climate Dynamics, 2015)

Oceanic factors controlling the Indian summer monsoon onset in a coupled model - Chloé Prodhomme; Pascal Terray; Sébastien Masson; Ghyslaine Boschat; Takeshi Izumo (Climate Dynamics, 2015)

Impacts of Indian Ocean SST biases on the Indian Monsoon: as simulated in a global coupled model - Chloé Prodhomme; Pascal Terray; Sébastien Masson; Takeshi Izumo; Tomoki Tozuka; Toshio Yamagata (Climate Dynamics, 2014)

Impact of climate change on the hydrogeology of two basins in northern France - Florence Habets; Julien Boé; Michel Déqué; Agnès Ducharne; Simon Gascoin; Ali Hachour; Eric Martin; Christian Pagé; Eric Sauquet; Laurent Terray; Dominique Thiéry; Ludovic Oudin; et al. (Climatic Change, 2013)

High resolution simulation of the South Asian monsoon using a variable resolution global climate model - T. P Sabin; R. Krishnan; Josefine Ghattas; Sebastien Denvil; Jean-Louis Dufresne; Frederic Hourdin; Terray Pascal (Climate Dynamics, 2013)

Intraseasonal SST-precipitation relationship and its spatial variability over the tropical summer monsoon region - Mathew Roxy; Youichi Tanimoto; B. Preethi; Pascal Terray; R. Krishnan (Climate Dynamics, 2013)

Impact of intra-daily SST variability on ENSO characteristics in a coupled model - Sébastien Masson; Pascal Terray; Gurvan Madec; Jing-Jia Luo; Toshio Yamagata; Keiko Takahashi (Climate Dynamics, 2012)

The role of the intra-daily SST variability in the Indian monsoon variability and monsoon-ENSO–IOD relationships in a global coupled model - Pascal Terray; Kakitha Kamala; Sébastien Masson; Gurvan Madec; A. K. Sahai; Jing-Jia Luo; Toshio Yamagata (Climate Dynamics, 2012)

Robustness of SST teleconnections and precursory patterns associated with the Indian summer monsoon - Ghyslaine Boschat; Pascal Terray; Sébastien Masson (Climate Dynamics, 2012)

Possible role of warm SST bias in the simulation of boreal summer monsoon in SINTEX-F2 coupled model - Susmitha Joseph; A. K. Sahai; B. N. Goswami; Pascal Terray; Sebastian Masson; J.-J. Luo (Climate Dynamics, 2012)

Interannual relationships between Indian Summer Monsoon and Indo-Pacific coupled modes of variability during recent decades - Ghyslaine Boschat; Pascal Terray; Sébastien Masson (Climate Dynamics, 2011)

Southern Hemisphere extra-tropical forcing: a new paradigm for El Niño-Southern Oscillation - Pascal Terray (Climate Dynamics, 2011)

Tidal mixing in the Indonesian Seas and its effect on the tropical climate system - Ariane Koch-Larrouy; Matthieu Lengaigne; Pascal Terray; Gurvan Madec; Sebastien Masson (Climate Dynamics, 2010)

African monsoon teleconnections with tropical SSTs: validation and evolution in a set of IPCC4 simulations - Mathieu Joly; Aurore Voldoire; Hervé Douville; Pascal Terray; Jean-François Royer (Climate Dynamics, 2007)

Impact of southeast Indian Ocean sea surface temperature anomalies on monsoon-ENSO-dipole variability in a coupled ocean–atmosphere model - Pascal Terray; Fabrice Chauvin; Hervé Douville (Climate Dynamics, 2007)